Pengaruh Leverage, Ukuran Perusahaan, Dan Komisaris Independen Terhadap Penghindaran Pajak Pada Perusahaan Retail Di BEI - Naufal Hafiz Haryono; Zirman Zirman; Donal Devi Amdanata (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to empirically examine the effect of leverage, company size, and independent board of commissioners on tax avoidance in retail companies listed on the Indonesia Stock Exchange (IDX). Tax avoidance is proxied using the Effective Tax Rate (ETR). This study uses a quantitative method with secondary data in the form of annual reports of retail companies classified as IDX-IC for the period 2021–2024. The sample was determined through purposive sampling and resulted in 14 companies with 56 observational data. After data transformation using square root and outlier elimination to meet the normality assumption, the final sample size was 46 data. The analysis was conducted using multiple linear regression with the help of SPSS 27. The results of the partial test (T-Test) showed that leverage had a significant effect on tax avoidance (ETR), while company size and independent board of commissioners had no significant effect. The coefficient of determination test showed that the independent variables were able to explain 10.3% of the variation in tax avoidance, while the remaining 89.7% was influenced by other factors outside the research model.